Efficiency Of Foreign Exchange Markets: A Developing Country Perspective - Wickremasinghe, Guneratne B (Asian Academy of Management (AAM), 2005)
This study tests weak and semi-strong form efficiency of the foreign exchange market in Sri Lanka during the recent float using six bilateral exchange rates. Weak-form efficiency is examined using unit root tests while semi-strong form efficiency is tested using cointegration, Granger causality tests and variance decomposition analysis. Results indicate that the Sri Lankan foreign exchange market is consistent with the weak-form of the efficient market hypothesis (EMH). However, the results provide evidence against the semi-strong version of the EMH. These results have important implications for government policy makers and participants in the foreign exchange market of Sri Lanka